Retinal Thickness Asymmetry in Highly Myopic Eyes with Early Stage of Normal-Tension Glaucoma - Pei-Wen Lin; Hsueh-Wen Chang; Yi-Chieh Poon (Journal of Ophthalmology)
Purpose. To investigate the retinal thickness asymmetry parameters of circumpapillary retinal nerve fiber layer (cpRNFL) and macular layers measured by spectral-domain optical coherence tomography in highly myopic (HM) patients with an early stage of normal-tension glaucoma (NTG). Methods. This cross-sectional study included 55 eyes of HM patients with early NTG and 37 eyes of HM normal participants. High myopia was defined as spherical equivalence more myopic than −6 diopters. Thickness differences and asymmetry indices (AIs) of cpRNFL between superior and inferior corresponding parts and thickness differences and AIs of the total macular layer (TML) and inner macular layers between superior and inferior hemispheres were calculated. The areas under the receiver operating characteristic curves (AROCs) were analyzed and compared. Results. In the cpRNFL asymmetry analysis, the thickness differences and AIs of cpRNFL between temporal-superior and temporal-inferior sectors (P < 0.0001 and P < 0.0001, respectively) and between superior and inferior quadrants (P = 0.002 and P < 0.0001, respectively) were significantly different between HM control subjects and HM NTG patients. In the macular asymmetry analysis, the thickness difference and AI of TML were significantly different between superior and inferior hemispheres (P < 0.0001 and P < 0.0001, respectively). The thickness difference and AI of the macular ganglion cell layer (mGCL) were significantly different between superior and inferior hemispheres (P < 0.0001 and P < 0.0001, respectively). The AROCs for thickness difference of TML (0.845) and thickness difference of mGCL (0.773) were comparable to AROCs for average cpRNFL thickness (0.842), macular retinal nerve fiber layer thickness (mRNFL) thickness (0.871), and mGCL thickness (0.822). Conclusion. In our study, HM NTG patients had retinal thickness asymmetry in cpRNFL, TML, and mGCL. The diagnostic capabilities for thickness asymmetry of TML and mGCL were comparable to the diagnostic capabilities for cpRNFL thickness, mRNFL thickness, and mGCL thickness. Asymmetry analysis of retinal thickness can be an adjunctive tool for the early detection of HM NTG.